2015
DOI: 10.1089/ten.tea.2014.0267
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of Peripheral Blood-Derived Mesenchymal Stem Cells and Endothelial Progenitor Cells on Strontium-Doped Calcium Polyphosphate Scaffolds to Generate Vascularized Engineered Bone

Abstract: Vascularization of engineered bone tissue is critical for ensuring its survival after implantation and it is the primary factor limiting its clinical use. A promising approach is to prevascularize bone grafts in vitro using endothelial progenitor cells (EPC) derived from peripheral blood. Typically, EPC are added together with mesenchymal stem cells (MSC) that differentiate into osteoblasts. One problem with this approach is how to promote traditional tissue engineering bone survival with a minimally invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…Knowing that endothelial cells and EPCs can induce the osteogenic differentiation of MSCs [Thébaud et al, 2012;Fu et al, 2015], we measured the early osteogenic differentiation marker ALP as well as the concentration of the osteogenic growth factor BMP-2. In the pertinent literature, ALP is described as an early osteogenic differentiation marker.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that endothelial cells and EPCs can induce the osteogenic differentiation of MSCs [Thébaud et al, 2012;Fu et al, 2015], we measured the early osteogenic differentiation marker ALP as well as the concentration of the osteogenic growth factor BMP-2. In the pertinent literature, ALP is described as an early osteogenic differentiation marker.…”
Section: Discussionmentioning
confidence: 99%
“…The key contribution of cell milieu is supported by a great deal of research, part of which related to the sophisticated mimicking of structural and functional details of the extracellular matrix with artificial of semi-synthetic materials. (Cao et al, 2014;Fu et al, 2014;Shim, Ankeny, Kim, Nerem, & Khang, 2014;Tanase et al, 2013;Yeatts et al, 2014;Q. Zhao et al, 2010).…”
Section: Integrating the System: 2d And 3d Co-culturesmentioning
confidence: 99%
“…The feasibility of co-culture or co-implantation strategies has been so far tested in several studies, focusing on the quality of the engineered bone substitute (Dariima, Jin, Lee, Wall, & Kim, 2013;Fu et al, 2014;Kokemüller et al, 2014;Leszczynska et al, 2013;R P Pirraco et al, 2013;Rogério P Pirraco et al, 2014). Interestingly, mineralization can be achieved without osteogenic media or additional growth factors through co-cultures of normal human primary osteoblats and Human umbilical vein ECs (HUVECs) mainly by recurring to the manipulation of the coculture ratio (Shah, Wenke, & Agrawal, 2014).…”
Section: Integrating the System: 2d And 3d Co-culturesmentioning
confidence: 99%
“…Studies demonstrated that co-cultured EPCs and BMSCs could enhance bone regeneration 14, 24, 25 . However, no consensus on the condition for co-culture has been achieved 26 . In order to determine the best ratio of co-culture for bone regeneration, we co-cultured EPCs and BMSCs at ratios of 1:0, 10:1, 5:1, 1:1, 1:5, 1:10 and 0:1.…”
Section: Discussionmentioning
confidence: 99%